Cubic autocatalysis-based activation energy and thermophoretic diffusion effects of steady micro-polar nano-fluid - Singkibud, Peerapongpat; Sabir, Zulqurnain; Al Nuwairan, Muneerah; Sadat, R.; Ali, Mohamed R. (Microfluidics and nanofluidics, 2022)
Cubic catalysts are very crucial in the fluid mechanics due to the chemical processes boosted with less energy. Cubic catalysts in the chemical process have numerous applications in the chemical engineering and food industry, like transformation or storage of different types of food materials, turning raw materials into useful products and accelerate the rate of food formation processes. This article brings the numerical analysis of the activation energy along with the impacts of the chemical process using the micro-polar nano-fluid subject to the cubic autocatalysis. Furthermore, thermophoretic diffusion and Brownian motion have also been investigated in this work. The set of equations of motion, temperature, concentration, and angular momentum in the differential form along with the associated boundary conditions has been presented for micro-polar nano-fluid. The similarity variables are being utilized for the conversion of ordinary differential equations (ODEs) into the partial differential equations (PDEs). A familiar shooting technique is applied to convert the boundary conditions into the initial value problems and further the first kind of obtained ODEs numerically handled by the bvp4c procedure. Moreover, the physical parameters with the profiles of velocity, temperature and concentration along with the physical quantities of couple stress and local skin friction have been discussed.